2018
DOI: 10.1016/j.urology.2018.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Predictors of Testis Atrophy After Surgery for Testis Torsion in Children

Abstract: Based on the high atrophy rate, orchiectomy can be considered for testes that are black or hemorrhagic 5 minutes after detorsion. Pain duration >12 hours and parenchymal heterogeneity on preoperative ultrasound were also associated with testis atrophy. Red scrotal skin was not a reliable predictor of atrophy and should not delay exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 22 publications
1
48
0
3
Order By: Relevance
“…Preoperative risk factors associated with future testicular atrophy are pain duration for 12 hours or more, heterogeneous echogenicity of testicular parenchyma, and red scrotal skin [8]. All patients whose testes had a sudden blackened or hemorrhagic appearance five minutes after detorsion had more than 80% volume loss [8]. In one of our cases, testis size after torsion gradually decreased and revealed heterogeneous echogenicity on follow-up ultrasonography (Fig.…”
Section: Testicular Torsionmentioning
confidence: 66%
See 1 more Smart Citation
“…Preoperative risk factors associated with future testicular atrophy are pain duration for 12 hours or more, heterogeneous echogenicity of testicular parenchyma, and red scrotal skin [8]. All patients whose testes had a sudden blackened or hemorrhagic appearance five minutes after detorsion had more than 80% volume loss [8]. In one of our cases, testis size after torsion gradually decreased and revealed heterogeneous echogenicity on follow-up ultrasonography (Fig.…”
Section: Testicular Torsionmentioning
confidence: 66%
“…Testicular atrophy is a significant complication of testicular torsion. Preoperative risk factors associated with future testicular atrophy are pain duration for 12 hours or more, heterogeneous echogenicity of testicular parenchyma, and red scrotal skin [8]. All patients whose testes had a sudden blackened or hemorrhagic appearance five minutes after detorsion had more than 80% volume loss [8].…”
Section: Testicular Torsionmentioning
confidence: 99%
“…Intra-operative decision to remove or not the twisted testicle was based on the recoloration of the testicle after detorsion. In general, orchiectomy was performed for testicles that were black or hemorrhagic 5 min after detorsion [7]. Only patients who underwent surgery on the same day of presentation in the hospital were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of necrosis increases exponentially after 6 h of ischemia [26]. Grimsby et al [7] have showed that patients with symptom duration over 12 h have a testis volume loss of 88% compared with the normal contralateral testis. Thus, understanding the factors that influence delays to presentation and treatment is crucial to testicular survival after torsion.…”
Section: Influence Of Prehospital and In-hospital Times On Testicularmentioning
confidence: 99%
“…Currently, there is no standard definition of TA. We used a similar definition as suggested by relevant references ( 7 , 8 ); TA was defined as the following: TVL ≥80% or no sustained blood supply in the follow-up.…”
Section: Methodsmentioning
confidence: 99%